STRATEGI PEMASARAN PRODUK MOULDING BERBAHAN BAKU KAYU JATI PUTIH Gmelina arborea DENGAN PENDEKATAN BAURAN PEMASARAN - Muhammad Tahnur; Supratman Supratman; Bakri Bakri (Jurnal Ecogreen, 2015)
The change of raw material compositions (diameter and types) results in sufficient raw materials supply for moulding industry . The aims of research are (1) to describe the Jati putih (Gmelina arbore) wood product moulding marketing strategy at this moment. (2) to analyze the implementation of marketing mix  in developing the marketing of  products made from jati putih (gmelina arborea) moulding. The research was conducted at PT. Fauzan jaya and UD. Berua jaya. Both companies are located in Tallo district of Makassar as the centre of moulding products processing into a framework and a sofa-spring of the type of Jati putih (gmelina arborea). The method of the study is a qualitative descriptive studying the marketing strategy for products of Jati putih (gmelina arborea) moulding. Data where obtained from producers for strategy they use and from the customers for the success of the producers strategy. Analysis of current marketing strategy is also conduct to identify the current employed strategy, the success level of the strategy and the development of marketing strategies with marketing mix. The results of the research indicated that the strategy for the product is brand strategy, pricing strategy is an economy strategy, the distribution strategy is direct distribution, promotion strategy is personal selling and the product life cycle is introduction strategy.) Those strategies are practiced currently. Indicators of the success of the strategies are: brand awareness, market share, customer satisfaction  which all give an overview of necessary development of marketing strategy by diversifying products and after-sales services (product strategy), increasing the price bargaining power with quality improvement (pricing strategy), intensify the distribution and production locations closer to the consumer / factory (distribution strategy), the increase in personal selling and educate the market with the advantages of the Jati putih (gmelina arborea) (promotion strategy) and increase position of the product life cycle curve of the introductory stage to the growth stage. Keyword : marketing strategy, jati putih, marketing mix